Importance of the diagnosis and treatment of mesiodens in a pediatric patient: case report - da Silveira, Danieli Londero; da Silva, Cáren Coronel; dos Santos, Bianca Zimmermann; Pinto, Alice Souza (Disciplinarum Scientia | Saúde, 2021)
This study presents the clinical case of an eight-year-old male patient who visited the Pediatric Dentistry Clinic of Ingá (UNINGÁ) complaining of dissatisfaction with his smile. The clinical and radiographic examination revealed a supernumerary tooth between the maxillary central incisors (mesiodens). Treatment consisted of surgical removal of the mesiodens and restorative clinical interventions. The patient was then sent for orthodontic treatment for complete functional and esthetic restoration. This work addresses the etiology, diagnosis, incidence/prevalence, treatment according to location and age group as well as clinical and radiographic aspects of mesiodens. The present case shows that, when planned in an integrated manner and performed on a properly selected patient, the surgical removal of mesiodens achieves satisfactory results and improves the child’s quality of life.